Today I Learned

(back up to December)

December 30th

Today I learned more formally about proving propositions as types. The idea is that we can "prove'' a proposition by exhibiting an element which witnesses to a type which communicates the proposition. The idea is a bit abstract. Anyways, here is the table of translations.\[\begin{array}{c|c} \text{Logic} & \text{Type theory} \\ \hline 0 & \text{False} \\ 1 & \text{True} \\ A\land B & A\times B \\ A\lor B & A+B \\ A\to B & A\to B \\ A\leftrightarrow B & (A\to B)\times(B\to A) \\ \lnot A & A\to0 \\ \hline \forall x:A,\,P(x) & \prod_{x:A}P(x) \\ \exists x:A,\,P(x) & \sum_{x:A}P(x)\end{array}\]Many of these make some intuitive sense. For example, in type theory, $A\land B$ should hold if and only if we can exhibit a witness of both $A$ and $B.$ So our witness for $A\land B$ should be the ordered pair of the witnesses, which would be anything in $A\times B.$ Similarly, a witness of $A\lor B$ is something in $A$ or $B,$ which witnesses exactly $A+B.$ The $\forall$ and $\exists$ statements are similar.

Somewhat awkward (but nice) is the handling of $A\to B.$ Essentially, we're saying that $A$ implies $B$ if and only if exhibiting a witness of $A$ lets us exhibit a witness to $B.$ Well, that only happens (in type theory) if we can exhibit the exact function $A\to B$ taking witnesses of $A$ to $B.$

Let's see a proof. Let's show\[((A+B)\to0)\to(A\to0)\times(B\to0).\]Logically, this reads, $\lnot(A+B)\to\lnot A\land\lnot B,$ which is one of de Morgan's Laws. To "prove'' this statement, we just have to exhibit a function of the above type.

We begin with a logical proof, and we'll translate it to type theory. We first show $\lnot A.$ Well suppose for the sake of contradiction $A.$ Then $A+B,$ which is a contradiction by hypothesis. We second show $\lnot B.$ Well suppose for the sake of contradiction $B.$ Then $A+B,$ which is a contradiction by hypothesis. So we know $\lnot A$ and $\lnot B,$ from which $\lnot A\land\lnot B$ follows.

Now for type theory. The logical proof begins by showing $\lnot A,$ which we means we start by wanting a function $f_A:A\to0.$ Then we remark we are given $f:A+B\to0,$ from which $A\to0$ should follow. To write this out in type theory, we think categorically, and note\[A\stackrel{\op{inl}}\longrightarrow A+B\stackrel f\longrightarrow0\]will do the trick. That is, we can set $f_A=f\circ\op{inl}:A\to0,$ as desired.

Next we do similar for $\lnot B.$ We need to inhabit $B\to0,$ but we already have $A+B\to0,$ so\[A\stackrel{\op{inr}}\longrightarrow A+B\stackrel f\longrightarrow0\]will do the trick. That is, we can set $f_B=f\circ\op{inr}:B\to0,$ as desired.

The proof finishes by combining $\lnot A$ and $\lnot B$ to get $\lnot A\land\lnot B.$ In type theory, this means we need to combine our $f_A:A\to0$ and $f_B:B\to0$ to exhibit a witness in $A\times B\to0.$ For this, we can simply say\[(f_A,f_B):(A\to0)\times(B\to0)\]is such an ordered pair.

The proof is now finished, but it is somewhat satisfying to see it put together. Namely, we claim that\[g\equiv\lambda f.\big(\lambda(a:A).f\circ\op{inl}(a),\lambda(b:B).f\circ\op{inr}(b)\big):((A+B)\to0)\to(A\to0)\times(B\to0).\]is our witness. It suffices to show that, given $f:((A+B)\to0),$ $g(f):(A\to0)\times(B\to0).$ For this, because ordered pairs are primitive, we just need to show that each component function has the correct type. Well,\[\lambda a.f\circ\op{inl}(a):A\to0\]because it takes $a:A$ to $\op{inl}(a):A+B$ to $f(\op{inl}(a)):0,$ as needed. Similar holds for the $B\to0$ component, so we're done here.